Induction of ER and mitochondrial stress by the alkylphosphocholine erufosine in oral squamous cell carcinoma cells - Ansari, Shariq S.; Sharma, Ashwini Kumar; Soni, Himanshu; Ali, Doaa M.; Tews, Björn; König, Rainer; Eibl, Hansjörg; Berger, Martin R. (Cell death & disease, 2018)
Endoplasmic reticulum (ER) plays an essential role in cell function and survival. Accumulation of unfolded or misfolded proteins in the lumen of the ER activates the unfolded protein response (UPR), resulting in ER stress and subsequent apoptosis. The alkylphosphocholine erufosine is a known Akt-mTOR inhibitor in oral squamous cell carcinoma (OSCC). In the present study, we evaluate erufosine’s role to induce ER and mitochondrial stress leading to autophagy, apoptosis, and ROS induction. The cellular toxicity of erufosine was determined in two OSCC cell lines and gene expression and enrichment analyses were performed. A positive enrichment of ER stress upon erufosine exposure was observed, which was verified at protein levels for the ER stress sensors and their downstream mediators. Knockdown and pharmacological inhibition of the ER stress sensors PERK and XBP1 revealed their involvement into erufosine’s cellular effects, including proliferation, apoptosis, and autophagy induction. Autophagy was confirmed by increased acidic vacuoles and LC3-B levels. Upon erufosine exposure, calcium influx into the cytoplasm of the two OSCC cell lines was seen. Apoptosis was confirmed by nuclear staining, Annexin-V, and immunoblotting of caspases. The induction of mitochondrial stress upon erufosine exposure was predicted by gene set enrichment analysis (GSEA) and shown by erufosine’s effect on mitochondrial membrane potential, ATP, and ROS production in OSCC cells. These data show that ER and mitochondrial targeting by erufosine represents a new facet of its mechanism of action as well as a promising new framework in the treatment of head and neck cancers.